DO LUTO À LUTA, DAS RUAS ÀS REDES: SOBRE O QUE FALAM AS ATIVISTAS DO MOVIMENTO MÃES DE MAIO? - EVELISE COUTO MORAES (2024)
This master's dissertation investigates how the Movement Mães de Maio uses digital social networks for mobilization and which themes, besides the movement and the Crimes of May, are currently relevant to the activists. The chosen methodology was Categorical Content Analysis (Sampaio; Lycarião, 2021). The analysis was based on posts from the movement's Facebook page between April, May, and June 2022, totaling 146 posts classified into various categories, including "themes." The research revealed that the most highlighted topic was violence and its ramifications, such as police violence, violence against youth and children, women, Black people, the LGBTIAP+ community, and Indigenous peoples. Considering Certeau's (1998) concepts, it is concluded that the movement uses social networks tactically rather than strategically. To achieve these results, it was necessary to conduct an in-depth interview with Débora Maria da Silva, the founder of the movement, and revisit concepts about social movements from Gohn (2014), Vizer (2007), and Castells (2013).